Effects of Salt and Homogenization Processing on the Gastrointestinal Fate of Micro/Nano-Sized Colloidal Particles in Bigeye Tuna (Thunnus obesusis) Head Soup: In vitro Digestion Study - Lin, Liu; Cao, Zhenhai; Zhang, Xuebing; Kang, Ming; Wang, Xichang; Zhong, Jian; Xu, ChangHua; Zhang, Long; Tao, Ningping; Deng, Shanggui (Frontiers in Nutrition, 2022)
The effects of condiment (salt) and processing technic (homogenization) on digestion and interfacial properties of micro/nano-sized colloidal particles (MNCP) in bigeye tuna head soup (BTHS) using simulated gastrointestinal digestion model in vitro were investigated. For MNCP in BTHS, the triglycerides were wrapped with proteins in the form of ring. After salting, the average particle size of the MNCP in salted BTHS (SBTHS) decreased compared with BTHS. However, the local demulsification phenomenon existed, and part of the protein was encapsulated in some MNCP. After further homogenization, the average particle size of the MNCP in homogenous SBTHS (HSBTHS) was further decreased based on SBTHS and the MNCP was rearranged, which changed the original membrane structure. After gastrointestinal digestion, adding salt decreased the release of total fatty acids compared with unsalted. But homogenization processing increased the release of total fatty acids in HSBTHS and there was no significant difference (p0.05) between HSBTHS and BTHS. Thus, the decrease in the release of some fatty acids due to adding salt was compensated by homogenization. Therefore, the changes in composition and microstructure of MNCP induced by salt and homogenization might contribute to the digestion difference of MNCP.